2012
DOI: 10.2174/157340612800493719
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Activity of Novel Benzimidazole and Benzothiazole Derivatives against HepG2 Liver Cancer Cells

Abstract: Most of cancer chemotherapeutics and chemopreventives exert their effects by triggering apoptotic cell death. In this study, novel benzimidazole and benzothiazole derivatives have been synthesized to investigate their effects on HepG2 liver cancer cell lines after initial screening study. A dose response curve was constructed and the most active derivatives were further studied for apoptotic analysis. Six active benzimidazole derivatives (8, 9, 10, 12, 13 and 14) significantly induced apoptosis compared to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…The compounds 29 and 30 exhibited no activity (Table 3). Interestingly, the current results are in agreement with previous studies, which showed that some synthesized derivatives of benzothiazole and benzimidazole possessed noticeable anticancer activity (Youssef et al, 2012;Xiang et al, 2012).…”
Section: Anticancer Evaluationsupporting
confidence: 93%
“…The compounds 29 and 30 exhibited no activity (Table 3). Interestingly, the current results are in agreement with previous studies, which showed that some synthesized derivatives of benzothiazole and benzimidazole possessed noticeable anticancer activity (Youssef et al, 2012;Xiang et al, 2012).…”
Section: Anticancer Evaluationsupporting
confidence: 93%
“…In vitro antiproliferative activity of benzimidazole and benzothiazole derivatives against human melanoma cells (SK-Mel 5) was evaluated. Since benzimidazoles are recognized as potential anticancer drugs [ 10 ], we have also decided to examine the antiproliferative activity on other human cancer cells, including human T-lymphocyte cells (CEM), human cervical carcinoma cells (HeLa) and human pancreatic carcinoma cells (Mia Paca-2). Compound concentrations required to inhibit cell proliferation by 50% (in µM) are reported in Table 5 .…”
Section: Resultsmentioning
confidence: 99%
“…They are often found in large percentage in biomolecules like enzyme, vitamins and natural products [ 6 ]; for these reasons heterocyclic compounds remain the challenging issue for the researchers for the development of novel drugs [ 7 ]. Moreover, five membered-rings fused with benzene moiety attracted the attention of medicinal chemists especially benzimidazoles due to their diverse biological activities including antitumor [ 8 , 9 , 10 , 11 , 12 ], antifungal [ 13 ], anthelmintics [ 14 ], anti-inflammatory [ 15 ], analgesics [ 16 ] and antiviral [ 17 ]. Compounds belonging to this class of heterocycles are considered privileged due to their broad spectrum pharmacological activities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of drug candidates used in different therapeutic areas contain the benzimidazole ring such as antihypertensives, proton pump inhibitors, anti histaminics, anti helmintics. Compounds bearing benzimidazole moiety are reported to possess a number of interesting biological activities such as anticancer [1][2][3][4] , anthelmintic [5][6][7] , antiallergic [8][9] , antitubercular [10][11][12] , antioxidant [13][14] , antihistaminic [15][16][17] and antimicrobial [18][19][20][21][22][23][24][25][26][27] etc. There is a growing interest in the medicinal potential of natural products such as glycosides, alkaloids, flavones, coumarins etc.…”
Section: Introductionmentioning
confidence: 99%